BIJAK BERMEDIA SOSIAL, EDUKASI LITERASI DIGITAL UNTUK MENGURANGI DAMPAK NEGATIF DUNIA MAYA - Suworo Suworo; M Fauzan H M; Meta Yolanda; Khoirul Ardi Yansah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The rapid development of social media has provided significant benefits in terms of information access and communication; however, it has also generated various negative impacts such as the spread of misinformation, hate speech, cyberbullying, and low digital ethics awareness. These challenges highlight the importance of digital literacy education in fostering responsible and wise social media behavior. This study aims to analyze the effectiveness of digital literacy education in reducing the negative impacts of the online environment and enhancing users’ awareness and understanding of responsible social media use. The research employed a participatory educational approach through digital literacy socialization and educational activities, involving participants as the main subjects. Data were collected through observation, documentation, and evaluations conducted before and after the program implementation. The results indicate a significant improvement in participants’ understanding of social media ethics, information evaluation skills, and awareness of the negative consequences of irresponsible digital behavior. The digital literacy education program was proven to encourage positive behavioral changes and promote responsible social media usage. This study contributes to the development of digital literacy education programs as a preventive strategy to minimize the negative impacts of the digital environment in society.